The Relationship between Nerve Growth Factor and Vitamin B12 as a Predictive Marker for Nerve Damage in Iraqi Patients with Systemic Lupus Erythematosus - Farhan , Zaman B.; Abass, Eiman A A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Determination of serum nerve growth factor (NGF) and vitamin B12 in Iraqi female patients with systemic lupus erythematosus (SLE) and assessment of the effect of disease duration on the development of nerve damage. In addition, NGF may be a predictive marker for nerve damage in SEL patients. The current study included 130 individuals whose ages ranged from 18 to 48 years old, 100 of whom were female patients with SLE and 30 individuals as controls. Each patient was diagnosed after undergoing a thorough clinical evaluation backed by laboratory testing by a board-certified rheumatologist. The patients were classified according to the duration of disease into 15 patients with a disease duration of less than 3 months (G1), 29 patients with a disease duration of 1 year (G2), and 56 patients with a disease duration of more than one year (G3). This study showed a significant increase in serum NGF and a significant decrease in vitamin B12 levels in SLE patient groups when compared with control, as well as their level in SLE patients compared with control. Also, there was an essential negative correlation between NGF and vitamin B12 in SLE patients and controls. The present results found that the serum NGF levels in SLE patients considerably increased with the duration of the disease. Therefore, NGF may be a diagnostic and follow-up marker of the development of disease. In addition, the significant negative correlation between NGF and vitamin B12 indicates that SLE patients may be prone to nerve damage, and NGF may be a predictive biochemical marker for the development of nerve damage in SLE patients.